Burden of Nursing Home-Onset Clostridium difficile Infection in the United States: Estimates of Incidence and Patient Outcomes. (18th January 2016) - Hunter, Jennifer C.; Mu, Yi; Dumyati, Ghinwa K.; Farley, Monica M.; Winston, Lisa G.; Johnston, Helen L.; Meek, James I.; Perlmutter, Rebecca; Holzbauer, Stacy M.; Beldavs, Zintars G.; Phipps, Erin C.; Dunn, John R.; et al.
Abstract: Background. Approximately 4 million Americans receive nursing home (NH) care annually. Nursing home residents commonly have risk factors for Clostridium difficile infection (CDI), including advanced age and antibiotic exposures. We estimated national incidence of NH-onset (NHO) CDI and patient outcomes. Methods. We identified NHO-CDI cases from population-based surveillance of 10 geographic areas in the United States. Cases were defined by C difficile -positive stool collected in an NH (or from NH residents in outpatient settings or ≤3 days after hospital admission) without a positive stool in the prior 8 weeks. Medical records were reviewed on a sample of cases. Incidence was estimated using regression models accounting for age and laboratory testing method; sampling weights were applied to estimate hospitalizations, recurrences, and deaths. Results. A total of 3503 NHO-CDI cases were identified. Among 262 sampled cases, median age was 82 years, 76% received antibiotics in the 12 weeks prior to the C difficile -positive specimen, and 57% were discharged from a hospital in the month before specimen collection. After adjusting for age and testing method, the 2012 national estimate for NHO-CDI incidence was 112 800 cases (95% confidence interval [CI], 93 400–131 800); 31 400 (28%) were hospitalized within 7 days after a positive specimen (95% CI, 25 500–37 300), 20 900 (19%) recurred within 14–60 days (95% CI, 14 600–27 100), and 8700 (8%) died within 30 days (95% CI, 6600–10 700). Conclusions. Nursing home onset CDI is associated with substantial morbidity and mortality. Strategies focused on infection prevention in NHs and appropriate antibiotic use in both NHs and acute care settings may decrease the burden of NHO CDI.